2023
DOI: 10.3390/en16155585
|View full text |Cite
|
Sign up to set email alerts
|

Using the Magnetic Anisotropy Method to Determine Hydrogenated Sections of a Steel Pipeline

Abstract: The paper deals with a non-destructive method of detecting hydrogenated sections of pipelines, which is based on variations of the level of mechanical stresses generated in the surface layers of the steel pipe material during its hydrogenation. The use of a magnetoanisotropic method based on the phenomenon of metal magnetoelastic anisotropy development, which consists in the variation of the magnetic properties of ferromagnetic materials in direction and magnitude under the influence of mechanical stresses, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…We also conducted a series of simulations with duration of 60 s with type 3 of corrugated lining for several steel grades having different hardness and wear resistance V i , defined by Bolobov et al [18] (Table 2). According to the previously described methodology, the parameters E t and K were determined for each material.…”
Section: Lining Wear Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…We also conducted a series of simulations with duration of 60 s with type 3 of corrugated lining for several steel grades having different hardness and wear resistance V i , defined by Bolobov et al [18] (Table 2). According to the previously described methodology, the parameters E t and K were determined for each material.…”
Section: Lining Wear Modelingmentioning
confidence: 99%
“…Studies have shown [15] that only a reduction in the front angle of the plate edge without reducing its height can seriously affect the efficiency of the grinding process, so the recommended wear rate at which the lining plate should be replaced is 10-20% by weight [16,17]. The problem of intensive wear is combated by manufacturing lifters from wear-resistant materials [18], applying various types of hardening treatments [19] and applying coatings [20].…”
mentioning
confidence: 99%
“…In addition to the above, the fuel and energy sector remains a common area of application relating to the use of FAEs in the 21st century, which is explained by the prerequisites of historical development [8][9][10]. On the one hand, sustainable global energy developments are now on the international agenda in the context of the transition to renewable energy technologies [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…There are two compression technologies available for hydrogen: reciprocating compressors and centrifugal compressors. For gas compression, reciprocating compressors are typically used for volume flow rates less than 0.472 m 3 /s [24]. Centrifugal compressors are the recommended choice for applications involving high flow rates.…”
Section: Introductionmentioning
confidence: 99%